Experimental and numerical investigations of tip vortex cavitation for the propeller of a research vessel, "The Princess Royal" - Yılmaz, Naz; Dong, Xiaoqian; Aktas, Batuhan; Yang, Chenjun; Atlar, Mehmet; Fitzsimmons, Patrick A. (Pergamon-Elsevier Science Ltd, 2020)
The present study includes experimental and numerical investigations on propeller cavitation phenomena, particularly the tip vortex cavitation, for the test cases conducted with the model propeller of the Newcastle University research vessel, "The Princess Royal". These test cases were recommended recently as the benchmark data for cavitation observations and noise measurements by the ITTC, and have been tested in a major round-robin campaign by eight cavitation tunnel/basin facilities around the world. This round-robin test campaign included the Newcastle Emerson Cavitation Tunnel where the first set of tests was conducted. This study presents further systematic measurements conducted in the Shanghai Jiao Tong University (SJTU) cavitation tunnel with this benchmark propeller in the open water conditions, including the cavitation observations, and tests for the tip vortex cavitation inception and desinence. Also, the study includes computational fluid dynamics (CFD) investigation to discuss the results of the experiments, especially the tip vortex cavitation, in a comparative manner. To simulate tip vortex cavitation, the newly developed adaptive mesh approach MARCS (Mesh Adaption Refinement Approach for Cavitation Simulations) was further enhanced. The results of the CFD computations using this approach showed good agreement with the results of the tunnel tests for the open water propeller performance characteristics, cavitation observations and tip vortex cavitation pattern, including its extent.
Keywords: Propeller cavitation; Tip vortex cavitation; Mesh adaption; Propeller performance; Cavitation tunnel tests; EFD; CFD